Comparison of dispersion characteristics of hollow-core photonic crystal fibers filled with aromatic compounds - Nguyen, Thi Thuy; Dang, Van Trong; Hoang, Trong Duc; Le, Tran Bao Tran; Le, Bao Xuan; Tran, Quoc Vu; Vo, Thi Minh Ngoc; Chu, Van Lanh (Hue University Journal of Science: Natural Science, 2021)
In this paper, hollow-core photonic crystal fibers (PCFs) infiltrated with benzene and nitrobenzene are designed and investigated. Their dispersion characteristics are numerically simulated. The results show that using the aromatic-compounds-filled hollow core of PCFs makes dispersion curves flat. In addition, the dispersion curves approach the zero-dispersion line closer than previously published dispersion curves of PCFs with toluene, thus significantly improving the supercontinuum generation to create the ultra-flat spectrum expansion.